MP15: Profile and circumstances of cycling injuries: Data from an urban emergency department. (15th May 2017) - Brubacher, J.R.; Yip, R.; Trajkovski, A.; Lam, C.; Sutton, G.; Liu, T.; Chan, H.
Abstract : Introduction: Cycling as a form of active transportation is popular in many urban communities. However, little is known about the prevalence and circumstances of cycling injuries, particularly injuries resulting from single bicycle crashes which are not recorded in road trauma surveillance systems based on police crash reports. This study aimed to examine the profile and circumstances of cycling injuries seen in an urban emergency department (ED).Methods: This was a cross-sectional historical chart review study. All injured patients attending our ED are electronically flagged according to mechanism of injury. We reviewed the medical charts of all ED visits in 2015 that were flagged as "Cyclist Injury" or "Fall" to identify all cyclists who were injured while travelling on public roads (including sidewalks). Off road injuries were excluded.Results: In 2015, a total of 6450 ED presentations were flagged as cyclist injury (n=694) or fall (n=5756), and 667 cycling injuries met our inclusion criteria. Of these, 73 (11%) were admitted to hospital. The most common mechanisms of injury were fall from bicycle (51%), crash into stationary object (16%), and collisions with moving motor vehicles (25%). Potential contributing factors included alcohol or drug impairment (11%), road hazards (9%), avoidance manoeuvre (5%) and dooring (3%), although the cause of the crash was generally poorly documented in the medical charts. The most common injured body regions were upper extremity (55%) followed by head and neck (34%). Most injuries were abrasions/lacerations and fractures.Conclusion: Two thirds of cyclist injuries in this series were caused by single bicycle incidents, events not captured in official road trauma statistics which are based on police crash reports. The large majority of injured cyclists were treated and released from the ED. In most cases, the cause of the crash was poorly documented. This data highlights the limitations of using police crash reports or hospital admission records for road trauma surveillance and the significant knowledge gap in our understanding of causative factors leading to cycling injuries.